Graphene‐Oxide‐Encapsulated Fe2O3 Nanoparticles with Different Dimensions as Lithium‐Ion Battery Anodes: The Morphology Effect of Fe2O3. Issue 33 (1st September 2022) - Shen, Shuwen; Lu, Jiaxin; Zhang, Siyuan; Wang, Sen; Miao, Zimu; Wang, Hongce; Qiao, Wenming; Ling, Licheng; Wang, Jitong
Abstract: Fe2 O3 is expected to be a favorable candidate to replace commercial graphite as anode for lithium‐ion batteries (LIBs), however, it is impeded by dramatic volume expansion during charge/discharge process. Morphology control strategies have been widely conducted to develop the tolerance of Fe2 O3 against the volume change. To investigate the morphology effect, herein, graphene oxide (GO) encapsulated Fe2 O3 nanoparticles with three microstructures of nano‐rods, nano‐sheets, nano‐polyhedrons were synthesized. The structure‐dependent electrochemical performance has been demonstrated. The 1D rod‐like nano‐Fe2 O3 alleviates the inherent wrinkle morphology of GO sheets, which construct a stable three‐dimensional composite structure. Therefore, the GO‐encapsulated rod‐shaped Fe2 O3 (Fe/GO‐r) exhibits excellent reversible capacity of 1168.3 mA h g −1 over 100 cycles at 200 mA g −1 . The investigation of lithium‐ion migration kinetics indicates that Fe/GO‐r presents the highest contribution rate of surface induced capacitance. This study contributes towards the design of well‐performing anode materials for LIBs by investigating the effect of material morphologies. Abstract : Fe2 O3 /GO composites with three morphologies were synthesized via adding different anions in the Fe 3+ −H2 O hydrothermal system. The GO‐encapsulated rod‐shaped Fe2 O3 (Fe/GO‐r) exhibits excellent reversible capacity of 1168.3 mA h g −1 over 100 cycles at 200 mA g −1 as well as remarkable rate performance as the anode electrode in lithium‐ion battery.